Youth Beyond the City Thinking from the Margins (Bristol Bristol University Press, 2022)
This interdisciplinary collection charts the experiences of young people in places of spatial marginality around the world, dismantling the privileging of urban youth, urban locations and urban ways of life in youth studies and beyond. Expert authors investigate different dimensions of spatiality including citizenship, materiality and belonging, and develop new understandings of the complex relationships between place, history, politics and education. From Australia to India, Myanmar to Sweden, and the UK to Central America, international examples from both the Global South and North help to illuminate wider issues of intergenerational change, social mobility and identity. By exploring young lives beyond the city, this book establishes different ways of thinking from a position of spatial marginality.
English
Keywords: Marginality; Mobility; Rural youth; Space; Youth; thema EDItEUR::J Society and Social Sciences::JH Sociology and anthropology::JHB Sociology; thema EDItEUR::J Society and Social Sciences::JH Sociology and anthropology::JHM Anthropology::JHMC Social and cultural anthropology; thema EDItEUR::R Earth Sciences, Geography, Environment, Planning::RG Geography::RGC Human geography